Characteristics of soil stabilizers and their effect on heavy metal mobility in soil - Tneh, Brenda E Tjeen (2023)
Heavy metals are highly toxic and can lead to human and environmental health issues which poses a global threat and most heavy metal contamination happens through soil contamination. Many soil remediation methods have been proposed and researched to treat heavy metal contaminated soils and organic or biomass-based soil stabilizers are preferred to be applied as immobilizer as they are relatively cheaper compared to other soil stabilizers and can be nutritious to crops. However, studies on immobilization efficiency and mechanism of biomass-based materials needs more supporting evidence. In this research, plant extract (TM) and alkaline lignin (LGN) were used as a biomassbased soil immobilizer on a multiple element contaminated soil which consist of cadmium (Cd), copper (Cu), lead (Pb) and zinc (Zn). It was found that contaminated soil samples treated with LGN has higher reduction in mobility compared to TM. The mobility of Cd, Cu, Pb and Zn was reduced by 10.30%, 6.97%, 2.81% and 8.31% respectively through treatment by LGN while 8.05%, 4.93%, 1.28% and 4.03% respectively for treatment through TM. Functional groups like hydroxyl groups, amide groups and oxalic acid were found through the analysis of both soil stabilizers from FTIR and HPLC which affects the heavy metal mobility.